Quantifying Child-Appeal: The Development and Mixed-Methods Validation of a Methodology for Evaluating Child-Appealing Marketing on Product Packaging - Mulligan, Christine; Potvin Kent, Monique; Vergeer, Laura; Christoforou, Anthea K; L'Abbé, Mary R (Université d'Ottawa | University of Ottawa, 2021)
There is no standardized or validated definition or measure of "child-appeal" used in food and beverage marketing policy or research, which can result in heterogeneous outcomes. Therefore, this pilot study aimed to develop and validate the child-appealing packaging (CAP) coding tool, which measures the presence, type, and power of child-appealing marketing on food packaging based on the marketing techniques displayed. Children (n = 15) participated in a mixed-methods validation study comprising a binary classification (child-appealing packaging? Yes/No) and ranking (order of preference/marketing power) activity using mock breakfast cereal packages (quantitative) and focus group discussions (qualitative). The percent agreement, Cohen's Kappa statistic, Spearman's Rank correlation, and cross-classification analyses tested the agreement between children's and the CAP tool's evaluation of packages' child-appeal and marketing power (criterion validity) and the content analysis tested the relevance of the CAP marketing techniques (content validity). There was an 80% agreement, and "moderate" pairwise agreement (κ [95% CI]: 0.54 [0.35, 0.73]) between children/CAP binary classifications and "strong" correlation (rs [95% CI]: 0.78 [0.63, 0.89]) between children/CAP rankings of packages, with 71.1% of packages ranked in the exact agreement. The marketing techniques included in the CAP tool corresponded to those children found pertinent. Pilot results suggest the criterion/content validity of the CAP tool for measuring child-appealing marketing on packaging in accordance with children's preferences.
Keywords: child-appealing marketing; food marketing; food packaging; marketing power; marketing techniques; marketing to kids; mixed methods; product packaging; validation